Plankton bioindicators of environmental conditions in coastal lagoons. (5th January 2017) - Hemraj, Deevesh A.; Hossain, Md A.; Ye, Qifeng; Qin, Jian G.; Leterme, Sophie C.
Abstract: Coastal lagoons are characterised by strong spatial gradient of environmental parameters, especially hypersalinity, and are prone to anthropogenic disturbance. The Coorong (South Australia) is an inverse estuarine coastal lagoon separated from the sea by sand dunes. It is exposed to extreme water quality changes that affect its aquatic communities. Here, we used plankton as indicators of extreme environmental fluctuations to monitor and manage the environmental health of such complex systems. We defined the relationship of different plankton communities with water quality fluctuations and determined plankton species suitable for monitoring the ecosystem health. Two distinct communities of phytoplankton and zooplankton were identified, with salinity and nutrients being the principal factors impacting species distribution. Thus, two sets of indicator species were selected based on the different communities observed. Polychaete and gastropod larvae were positive indicators, showing salinity range restriction of brackish to marine. The distribution Acartia cf. fancetti represented healthy hypersaline conditions (salinity 40–60), while Cyclophora sp. and Scrippsiella sp. were negative indicators, correlating with extreme salinity and ammonia levels. The implementation of planktonic organisms as environmental indicators provided a constructive tool for the management of ecosystem health of the Coorong and will be applicable to similar coastal lagoons. Highlights: We identify two distinct plankton communities in the Coorong. Salinity and nutrient are major factors shaping the communities. We identify two sets of positive and negative indicator species. We provide a tool for managing ecosystem health states of coastal lagoons.